Wages, Risk, and Profits in the Whaling Industry - Hohman, Elmo P. (Quarterly Journal of Economics, 1926)
I. Wages. — The lay system of wage payment, 641. — Partial shifting of industrial risk from entrepreneur to worker, but no corresponding change in the proportion of profits and wages, 644. — The fall of the fractional lay, 648. — Real wages further lowered by abuses and extortionate charges, 650. — Lack of incentive under the lay system, 651. — Cosmopolitan character of the whaling crews, 653. — Whaling properly regarded as a trade, 654. II. Risk. — The whaling entrepreneur preeminently a dealer in risks. — Three main types: labor, physical, and business risks, 655. — Extraordinary fluctuations in whaling cargoes, 657. — Measures designed to offset risks: the lay system, diversified ownership, marine insurance, 659. III. Profits. — Extreme fluctuations, 662. — Average profits, 663. — Normal rate of profit a modest one, 665. — Illustration of "prizes and blanks" theory, 666. — Relative proportions of profits and wages, 667. — Despite large element of chance, business ability essential for long-run success, 667.